PENERAPAN SISTEM MODULAR PADA PERANCANGAN BANGUNAN MULTI-FUNGSI BERTINGKAT - Maurina, Anastasia (TATANAN, 2015)
AbstractVertical Multi-Use Building (called BMFB) is a single building with multiple functions therein are arranged vertically. BMFB has a high level of function complexity and the demands of change and development of each of these functions, so that it is necessary to have the design of functional space system with high flexibility. To obtain the building design with high flexibility, the functional space and the building structure system can not be seen separately, but must be designed in an integrated way. Modular building system can be a media to integrate the functional space and structure system to meet the demands of flexibility in the building. The building function on BMFB of this research is the function of parking, office functions and functions of residential and also the structure system is limited to the conventional structure system (rigid frame system and wall bearing system).Research is done in stages, starting from the analysis of basic grid module which integrating the dimensions of human activity module and the dimensions of building materials. Followed by the analysis of functional space planning grid module and analysis of structural grid module, it will be integrated into the design grid of BMFB. The result of the analysis is concluded in the form of the design guidelines of BMFB.Implementation of the modular system will facilitate and accelerate the design process to integrate the functional space system between function and to integrate the functional space system and structure system, so that it can produce a suitable design for each function in it so the design can fulfill the demands of change, development and integration of these functions. In addition, the implementation of this modular system has a positive impact on the construction process which can minimize the use of materials and can be integrated effectively with prefabrication system. Key Words: modular, grid, structure, spatial system, mixed used building                                                                                                  AbstrakBangunan Multi Fungsi Bertingkat (BMFB) adalah bangunan tunggal dengan beberapa fungsi di dalamnya yang disusun secara vertikal. BMFB memiliki tingkat kompleksitas fungsi yang tinggi serta tuntutan untuk dapat mengakomodasi perubahan dan perkembangan dari setiap fungsi tersebut, sehingga memerlukan rancangan sistem ruang dengan fleksibilitas tinggi. Untuk memperoleh rancangan bangunan dengan fleksibilitas tinggi, sistem ruang dan struktur bangunan tidak dapat dipandang secara terpisah, melainkan harus secara terpadu. Sistem bangunan modular dapat menjadi media untuk mengintegrasikan sistem ruang dan struktur dalam memenuhi tuntutan fleksibilitas pada BMFB. Fungsi yang diakomodasi BMFB pada penelitian ini adalah parkir, kantor, serta hunian. Sistem struktur dibatasi pada sistem struktur konvensional (rangka/dinding pemikul).Penelitian ini dilakukan secara bertahap, dimulai dari analisis modul grid dasar yang mengintegrasikan modul dimensi aktivitas manusia dan dimensi material bangunan, dilanjutkan dengan analisis modul grid perencanaan fungsi ruang dan analisis modul grid struktural, kemudian diintegrasikan menjadi grid perancangan BMFB. Hasil analisis disimpulkan dalam bentuk pedoman perancangan BMFB.Penerapan sistem modular dalam perancangan akan mempermudah dan mempercepat proses perancangan dalam mengintegrasikan sistem ruang antar fungsi, serta sistem ruang dan sistem struktur sehingga dapat dihasilkan rancangan yang cocok untuk setiap fungsi (parkir, kantor dan hunian) dan dapat memenuhi tuntutan perubahan, pengembangan serta penggabungan dari fungsi-fungsi tersebut. Penerapan sistem modular berdampak positif terhadap proses pelaksanaan konstruksi, karena dapat mengefisienkan penggunaan material serta memungkinkan penerapan sistem prefabrikasi yang lebih efektif. Kata Kunci: sistem modular, grid, sistem struktur, sistem ruang, bangunan multi fungsi